4
$\begingroup$

This is a follow-up to a question posted recently. Let $$s_n = \sum_{r=1}^{n} \frac{1}{r(r+1)},$$ where we take $s_0 = 0$.

The problem I am interested in is this: For fixed $k \geq 2$, find all solutions $(m,n)$ in nonnegative integers to the Diophantine equation $$s_m - s_n = \frac{1}{k}.$$

Current state of knowledge (see the original question):

  1. $s_m - s_n$ can be expressed as $$s_m - s_n = \frac{m-n}{(m+1)(n+1)},$$

  2. At least some of the solutions are given by taking each divisor $a$ of $k$ such that $a > 1$ and setting $$m = (a-1)k-1,$$ $$n = \frac{(a-1)k}{a} - 1.$$

$\endgroup$
4
$\begingroup$

We are to solve $$\displaystyle \frac{1}{x} - \frac{1}{y} = \frac{1}{k}$$

This can be rearranged to

$$(k+y)(k-x) = k^2$$

So each divisor $\displaystyle a > k$ of $\displaystyle k^2$ will give a solution and all solutions are gotten by that. So just by taking divisors of $\displaystyle k$, you might be missing some solutions for many values of $\displaystyle k$

For instance for $\displaystyle k=15$ you will be missing the solution $\displaystyle m = 9, n = 5$

$\endgroup$
  • $\begingroup$ Excellent! For example, the construction I describe misses the solution (in your formulation) $x = 2$, $y = 3$ in the case $k = 6$, which comes from the factorization of $36 = 9 \cdot 4$. $\endgroup$ – Mike Spivey Oct 19 '10 at 6:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.